Chromatin in situ proximity (ChrISP): Single-cell analysis of chromatin proximities at a high resolution - Xingqi Chen; Chengxi Shi; Samer Yammine; Anita Göndör; Daniel Rönnlund; Alejandro Fernandez-Woodbridge; Noriyuki Sumida; Jerker Widengren; Rolf Ohlsson (BioTechniques)
Current techniques for analyzing chromatin structures are hampered by either poor resolution at the individual cell level or the need for a large number of cells to obtain higher resolution. This is a major problem as it hampers our understanding of chromatin conformation in single cells and how these respond to environmental cues. Here we describe a new method, chromatin in situ proximity (ChrISP), which reproducibly scores for proximities between two different chromatin fibers in 3-D with a resolution of ∼170Å in single cells. The technique is based on the in situ proximity ligation assay (ISPLA), but ChrISP omits the rolling circle amplification step (RCA). Instead, the proximities between chromatin fibers are visualized by a fluorescent connector oligonucleotide DNA, here termed splinter, forming a circular DNA with another circle-forming oligonucleotide, here termed backbone, upon ligation. In contrast to the regular ISPLA technique, our modification enables detection of chromatin fiber proximities independent of steric hindrances from nuclear structures. We use this method to identify higher order structures of individual chromosomes in relation to structural hallmarks of interphase nuclei and beyond the resolution of the light microscope.